The Influence of Social Environment on Mental Health of Pregnant Women at Tilongka Billa Community Health Center - Hastuti Hastuti; Sulistiyah Sulistiyah (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Background: Mental health during pregnancy is influenced by multiple factors, including the social environment. Family support, peer interactions, and community engagement are critical determinants of psychological well-being, yet their impact local community health settings remains underexplored. Objective: This study aimed examine the influence the social environment the mental health pregnant women Tilongka Billa Community Health Center. Methods: A quantitative correlational study was conducted with 70 pregnant women selected through purposive sampling. Data were collected using structured questionnaires assessing demographic characteristics, social support (family, peer, and community), and mental health status (Perceived Stress Scale and Edinburgh Postnatal Depression Scale). Descriptive statistics summarized the participants’ characteristics, while Pearson Spearman correlation tests analyzed relationships between social environment factors mental health outcomes (p < 0.05). Results: The results indicated that family support had the highest mean score (4.1 ± 0.7), followed by peer support (3.8 ± 0.8) and community involvement (3.5 ± 0.9). Mental health assessments revealed moderate stress levels (18.2 ± 5.0) and mild depression risk (9.5 ± 4.3). Correlation analysis showed significant negative relationships between social support and mental health indicators, with family support exhibiting the strongest correlation with reduced stress (r = -0.48, p = 0.002) and depression (r = -0.52, p = 0.001). Conclusion: The study demonstrates that supportive social environment, particularly family and peer support, plays crucial role in reducing stress and depressive symptoms among pregnant women. Strengthening social support networks through counseling, peer groups, and community engagement programs may enhance maternal mental health and promote positive pregnancy outcomes.